Uma revisão de literatura sobre a teoria dos conjuntos e o movimento da matemática moderna - Silva, Gabriela Egidio Penha (2021)
This dissertation consists of a literature review which aims at understanding the role of Set Theory in the proposals of the Modern Mathematics Movement, which reached its peak in the 1960s and 1970s. We studied the evolutions of Mathematics that served as inspiration for the Modern Mathematics Movement. We tried to understand the objectives and motivations of the movement, as well as its introduction in Brazil. We also related the demise of Modern Mathematics Movement, which occurred in the mid-1970s, as well as the legacy of the movement for the teaching of Mathematics. Based on textbooks and other sources, we concluded that Set Theory was believed to promote a uniform and rigorous treatment for Mathematics in elementary school, middle school and high school. In addition, we presented the main concepts and results on topics in Set Theory that were introduced in Basic Education curriculum by Modern Mathematics Movement.